NMR studies of polymeric sodium ion conductors—a brief review - Zheng, Allen; Greenbaum, Steven G. (Frontiers in Chemistry, 2023)
Sodium has long been considered an alternative active battery cation to lithium because of the chemical similarity and the overwhelming natural abundance of Na compared to Li. In the "early days" of poly(ethylene oxide) (PEO) and alkali metal salt complexes proposed as polymer electrolytes, studies of Na-salt/PEO materials were nearly as prevalent as those of lithium analogues. Fast forwarding to the present day, there is growing interest in sodium battery chemistry spurred by the challenges of continued advancement in lithium-based batteries. This article reviews the progress made in sodium-based polymer electrolytes from the early days of PEO to the present time. Other polymeric electrolytes such as gel polymer electrolytes (GPE), including formulations based on ionic liquids (ILs), are also discussed.